Optimal thermalcycleforproductionofglass–ceramic basedonwastes from ferronickelmanufacture - Ejup Ljatifi, AlexandraKamusheva, AnitaGrozdanov, PericaPaunović, Alexander Karamanov (My University, 2015)
Hazardouselectro-furnaceslag(EFS), dust(D) andconverterslag(CS) from ferronickel smelting plant were mixed with glass cullet and vitrified. The optimal heat-treatment regime for transformation of obtained glass into glass–ceramic was evaluated using fast alternative methods: the nucleation step was estimated by DTA analysis, while the crystallization step – by pycnometric measurements. Additional kinetics data, attained by non-isothermal heat-treatments at different heating rates, were also analyzed and the formed crystal phases were studied by XRDanalysis. The investigated glass is easily melted (2h at 1400 oC) and is characterized by a spontaneous tendency for bulk crystallization. In addition, due to the presence of 1.5 wt% Cr2O3 in the batch, supplementary nucleation process takes place, which is a premise for formation of fine crystalline structure and improved mechanical properties. The results elucidate that short heat-treatment atlow temperatures (45–60 min. nucleation atabout 650 oC and 30–45 mincrystallization at about 750 oC) leads to formation of mono-phase pyroxene glass–ceramic with ~50 wt% crystallinity.